The agrarian capitalist development in France - Vergara, Ricardo (1993)
The work follows French agricultural developments in 20Th century, emphasising the post-war period as an example of successful capitalist development to be emulated in order to expand the frontiers of agrarian research in Peru. Land divisions into parcels, in both cases, was a product of political land redistribution reforms. The study has three focuses: The contradiction between the slow rise in food demand in France and the rapid rise in productivity and production; the continued existence of land parcels -small and medium- as the predominant forms of ownership and the disappearance of land leases; the growing subordination of the farming sector to the needs and determinations of the farm and food industries​